2013
DOI: 10.1016/j.ab.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Selective tryptophan determination using tryptophan oxidases involved in bis-indole antibiotic biosynthesis

Abstract: A novel tryptophan assay was developed using tryptophan oxidases. Although many l-amino acid oxidases (LAAOs) have been reported to catalyze tryptophan oxidation, most of them have broad substrate specificity and oxidize multiple amino acids besides tryptophan. To obtain a tryptophan-specific LAAO, we focused on bis-indole antibiotic biosynthesis, a bacterial secondary metabolic pathway. A putative LAAO from Streptomyces sp. TP-A0274, StaO involved in staurosporine biosynthesis, was heterologously expressed, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The slope of this curve indicated that almost all of the added Arg was recovered by the assay, estimating the recovery rate to be 98%. Chromatographic analysis (Kameya et al 2013) estimated the Arg concentration in the same casamino acid solution to be 133 nM. This value is comparable to that estimated by the previous bioassay (140 nM), demonstrating the successful measurement of an amino acid in crude samples by this bioassay.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The slope of this curve indicated that almost all of the added Arg was recovered by the assay, estimating the recovery rate to be 98%. Chromatographic analysis (Kameya et al 2013) estimated the Arg concentration in the same casamino acid solution to be 133 nM. This value is comparable to that estimated by the previous bioassay (140 nM), demonstrating the successful measurement of an amino acid in crude samples by this bioassay.…”
Section: Resultssupporting
confidence: 74%
“…A variety of methods have been developed to meet these demands, such as instrumental methods (Kaspar et al 2009) and enzymatic assays Kameya et al 2013;Liu et al 2014;Matsui et al 2015). Among these analytical methods, amino acid bioassays have been popular over the past 70 years because of their low cost, easy manipulation, coverage of wide range of amino acids, and applicability to high-throughput analysis (Cardinal and Hedrick 1948;Steele et al 1949;Tamura et al 1952).…”
Section: Introductionmentioning
confidence: 99%
“…VioA enzyme kinetics were determined in a coupled peroxidase assay mainly as described previously (7,9). A reaction mixture of 600 l containing 50 mM Tris-HCl, pH 9.0, 0.2 M VioA, 1 mM 4-aminoantipyrine, 1 mM phenol, and 15 units/ml horseradish peroxidase was pre-incubated at 30°C.…”
Section: Vioa Activity Assaysmentioning
confidence: 99%
“…1) (7)(8)(9). Subsequently, oxidative coupling of two imines by VioB, RebD, or StaD results in the formation of a short-lived compound that was proposed to be an IPA imine dimer (7,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation